Analisis Bioautografi Kromatografi Lapis Tipis dan Aktivitas Antibakteri Ekstrak Etanol Bawang Tiwai (Eleutherine bulbosa (Mill.) Urb.) terhadap Methicillin-resistant Staphylococcus aureus (MRSA) - Swandari Paramita; Yadi Yasir; Yuniati Yuniati; Ibnu Sina (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2018)
Methicillin-resistant Staphylococcus aureus (MRSA) infections are the major health problem in Indonesia; this is mainly due to their resistance to antibiotics. Based on this, the quest for new sources of natural based antimicrobial drugs is necessary. Bawang tiwai (Eleutherine bulbosa (Mill.) Urb.) is one of the natural materials that have potential as an antibacterial natural-based of Indonesia origin. Bawang tiwai already used empirically by local communities in East Kalimantan to treat various diseases. The aim of this research is to know the antibacterial activity of E. bulbosa ethanol extract on MRSA and to know the type of secondary metabolite with antibacterial activity tested by TLC bioautography method. The experiment was conducted on Research Laboratory, Faculty of Medicine, Mulawarman University, Samarinda. TLC results showed that ethanol extract of E. bulbosa has compounds containing sugar, alkaloids, steroids, and flavonoids. The results of TLC bioautography show that ethanol extract of E. bulbosa can inhibit the growth of MRSA. MIC results show that ethanol extract of E. bulbosa has potent antibacterial activity against MRSA with MIC 1 mg/mL. The conclusion of this research is all the results support the potential of bawang tiwai as the alternative component of natural-based antibacterial agents against MRSA.